2011
DOI: 10.1021/ac102978f
|View full text |Cite
|
Sign up to set email alerts
|

Nonresonant Femtosecond Laser Vaporization with Electrospray Postionization for ex vivo Plant Tissue Typing Using Compressive Linear Classification

Abstract: Laser electrospray mass spectrometry (LEMS) with offline classification is used to discriminate plant tissues at atmospheric pressure using an intense (10(13) W cm(-2)), nonresonant (800 nm) femtosecond laser pulse to vaporize cellular content for subsequent mass analysis. The tissue content of the plant within the 0.05 mm(2) laser interaction region is vaporized into the electrospray plume where the molecules are ionized prior to transfer into the mass spectrometer. The measurements for a flower petal, leaf, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…If the nonequilbrium channel of vaporization occurs prior to thermalization to protein modes, dissociation can be avoided. In fact, the interaction of intense, nonresonant, femtosecond laser pulses (70 fs, 10 13 W∕cm 2 ) with a condensed phase sample at atmospheric pressure results in the intact vaporization of a wide variety of nonvolatile polyatomic molecules in systems ranging from explosive formulations to plant tissue (30)(31)(32)(33). The discovery that a strong field femtosecond laser pulse can transfer neu-tral macromolecules into the gas phase intact (34) was unanticipated because isolated molecules in vacuum exposed to an intense laser pulse will ionize and possibly fragment (35,36).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If the nonequilbrium channel of vaporization occurs prior to thermalization to protein modes, dissociation can be avoided. In fact, the interaction of intense, nonresonant, femtosecond laser pulses (70 fs, 10 13 W∕cm 2 ) with a condensed phase sample at atmospheric pressure results in the intact vaporization of a wide variety of nonvolatile polyatomic molecules in systems ranging from explosive formulations to plant tissue (30)(31)(32)(33). The discovery that a strong field femtosecond laser pulse can transfer neu-tral macromolecules into the gas phase intact (34) was unanticipated because isolated molecules in vacuum exposed to an intense laser pulse will ionize and possibly fragment (35,36).…”
mentioning
confidence: 99%
“…This nonlinear excitation implies that the sample preparation steps of elution and mixing with a matrix are not necessary. Direct analysis of molecules ranging in size from pharmaceuticals (∼300 Da) to proteins (>40 kDa) has been performed using the laser electrospray mass spectrometry (LEMS) method (13,(30)(31)(32)(33)(34) where ionization, mass analysis, and detection of the femtosecond laser-vaporized sample is achieved via atmospheric pressure ESI-TOF-MS.…”
mentioning
confidence: 99%
“…Unlike flower petal, peaks at m/z 145.0 and were also observed from the leaf as the petal. The unique profile of metabolites in the plant, including flavonoids, carbohydrates, and other metabolites, can serve as signatures for rapid sample screening and classification, e.g., discriminating different varieties of grapes (Accent, Dunkelfelder, and Dakapo) [52], phenotypes of Impatiens flower petals [33], and color patterns of a Zebra plant leaf [34], using laser desorption followed by electrospray postionization MS techniques and multivariate statistical analysis.…”
Section: Direct Analysis Of Plant Tissue By F-lems and Ti:sapphire-lementioning
confidence: 99%
“…LEMS does not require either the analyte or matrix to be linearly resonant with the laser wavelength and shows little dependence on the types of sample substrate employed [30]. Various biological samples, including chicken egg albumen and yolk [31], reduced fat and whole milk [32], whole blood [31,32], and plant samples [33,34] have been successfully characterized by LEMS without the use of external matrix. Investigations of animal tissue samples, a popular target of MS imaging, have not been performed so far by LEMS to examine the feasibility of femtosecond laser vaporization for chemical analysis of animal tissue samples.…”
Section: Introductionmentioning
confidence: 99%
“…LEMS couples nonresonant femtosecond (fs) laser vaporization with ES ionization to perform ambient pressure mass analysis on a wide variety of samples, including pharmaceuticals [35], lipids [36], narcotics [37], dipeptides [34], explosives [38][39][40], and plant tissues [41,42] for phenotype classification [41]. Most importantly, investigations of lysozyme and cytochrome c revealed that the solution-phase conformation was preserved during transfer to ES droplets when an intense, nonresonant ultrafast laser was employed for vaporization [43].…”
mentioning
confidence: 99%